Investidores institucionais e o financiamento da infraestrutura - uma estimativa do volume de recurso em potencial para o Brasil - Katia Rocha (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– This study aims to quantify the potential financing estilmates from institutional investors - pension funds, insurance companies, investment funds and sovereign wealth funds - from global (OECD) and domestic markets to infrastructure in Brazil. Institutional investors are not homogeneous, and have a wide range of objectives, characteristics and structural factors that influence their investment decisions, in addition to regulatory restrictions. The model covers: i) estimation of assets under management, considering structural restrictions on liquidity, size and profile by type of investor, which reduces the current volume by at least 50%; ii) increasing of 2% to 3% in portfolio allocation to infrastructure asset class for the next decade; iii) assets under management growth of 6% pa according to the historical data; and iv) Brazil's market share of 2.5% from global resources available for infrastructure. The potential financing for Brazil infrastructure from institutional investors corresponds of US 9 billion to US 17 billion pa in the next decade, equivalent of 0.5% to 0.9% of 2019 GDP. That figure, given the current investment levels of about 2% of GDP, leads to a potential flow of about 3% of GDP, a considerable amount, but still below the target of 4% of GDP (about US 70 billion per year). We emphasize that this exercise provides values that are justified only as an estimate of the order of magnitude and should be viewed sparingly and according to the hypotheses considered.
Keywords: G38; L51; F21; 330; institutional investors; infrastrucuture financing; infrastructure asset class